Crashworthiness design for foam-filled thin-walled structures with functionally lateral graded thickness sheets. (June 2015) - An, Xiuzhe; Gao, Yunkai; Fang, Jianguang; Sun, Guangyong; Li, Qing
Abstract: Crash components in automobiles are probably subjected to multiple loading conditions in real life, such as axial crushing and lateral bending. Unlike most of the existing work that solely focuses on the pure axial crushing or lateral bending, this paper attempts to accommodate both by proposing a novel structure, namely foam-filled thin-wall tube with functionally lateral graded thickness (FLGT). From numerical study of FLGT structures, they are found to exhibit noticeable advantage over the corresponding traditional uniform thickness (UT) structures with the same weight under both axial crushing and lateral bending. Moreover, the gradient governing the varying thickness shows significant influence on the crashworthiness performance of FLGT. To seek for the optimal gradient, a multi-objective optimization is carried out using multi-objective particle swarm optimization (MOPSO) algorithm, where response surface models are established to formulate the objectives functions, i.e. specific energy absorption (SEA) and peak impact force ( F peak ). The optimization results show that the foam-filled structure with FLGT can produce more promising Pareto solutions than traditional UT counterparts. Therefore, the FLGT structure could have potential applications subjected to different loading conditions. Highlights: A novel thin-wall structure with lateral graded thickness (FLGT) is proposed. The novel structure is found suitable for both axial crushing and lateral bending. Multi-objective optimization is conducted for the two loading cases. FLGT is more advantageous than corresponding uniform thickness counterpart.